Integrasi SMS Gateway Untuk Pengembangan Sistem Informasi Surat Pada Kantor Kepala Desa (Studi kasus: Desa Balapulang Kulon Kab. Tegal) - Arfan Haqiqi Sulasmoro; Indri Yunita Sari; Yerry Febrian Sabanise (Jurnal Informatika: Jurnal Pengembangan IT, 2018)
Village administration is part of the central government whose operations are aimed at rural areas. Village government is led by a village head, which is in charge of organizing the government, implementing community development, and also empowering the village community. Caused by the rush of community problem, a village head must be provided quick and accurate information to handle community problem. This research aimed to build an information system integrated with an SMS gateway to help both of village head and village administration staff to tackle community problem efficiently. The information system built by web-based mail management combined with MySQL database.